Indonesia Budget Deficit - Arien Sandra Olivia; Azwardi Azwardi; Anna Yulianita (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2018)
This study aims to determine the effect of Revenue and World Oil Prices on Deficit Budget (APBN) in 2007-2016. The data used in this research is secondary data from 2007-2016. Based on these objectives, the method of analysis used is multiple linear regression analysis.The results of this study tax revenues and world oil prices have simultaneouslyaffect toward the budget deficit. When viewed on an individual basis so influential in world oil prices. This is because world oil prices are fluctuating while the budget deficit keeps increasing year-on-year. World oil prices also contribute to the income tax of oil and gas where the current income tax decreased. While there is a significant tax revenue. This condition is caused by the contribution of tax revenue towards state revenues more than 60 percent.